Caracterização do estilo alimentar de crianças com perturbações alimentares - Viana, Victor (2008)
The aim of this research was to study comparatively the eating style of children with feeding disorders, normal-weight, over-weight and obese. 124 children from both gender, and age between 3 -13 were observed; 26 of them presented feeding disorders, 33 were normal-weight, 32 over-weight and 33 were obese. Children and their mothers were assessed about demographic factors and SES. Mothers answered to the Child Eating Behaviour Questionnaire. Results were statistically analysed with Linear Regression and Anova. The weight status of the mother and Emotional-over-eating (from CEBQ) were determinants of the children's weight status (Z score BMI). Satiety response and Slowness in eating were negatively associated with children's Z score BMI. The four groups were different in their eating style. Factors included in food attraction scale were positively associated with weight categories; factors classified in food avoidant scale were negatively associated. This research confirms the importance of the investigation of eating style in feeding disorders, and the contribution of the CEBQ for that subject. Key Words: Feeding-disorders, eating style, obesity.